2009
DOI: 10.1088/1751-8113/42/21/214044
|View full text |Cite
|
Sign up to set email alerts
|

Localization constraints in Gaussian wave packet molecular dynamics of nonideal plasmas

Abstract: The problem of wave packet broadening in the method of wave packet molecular dynamics simulations of electron–ion nonideal plasmas is discussed. It is shown that when using a harmonic restrictive potential for the packet widths, simulation results depend strongly on the constraint parameter. Two new approaches to constraining the packet broadening in a less stringent way are analyzed: periodic boundary conditions for widths and a dynamic constraint, based on filtering close particle collisions. These different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…The Gaussian ansatz seemed reasonable because at high temperatures, electrons were expected to approximate classical behavior [20]. However, electrons as simulated by WPMD feature divergent width parameters leading to wave packet spreading [22][23][24][25][26][27][28][29]. Electrons then overlap all ions, with no mechanism to localize near nuclei, producing a nearly constant electron background at large times.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Gaussian ansatz seemed reasonable because at high temperatures, electrons were expected to approximate classical behavior [20]. However, electrons as simulated by WPMD feature divergent width parameters leading to wave packet spreading [22][23][24][25][26][27][28][29]. Electrons then overlap all ions, with no mechanism to localize near nuclei, producing a nearly constant electron background at large times.…”
mentioning
confidence: 99%
“…Morozov and Valuev [29] showed that by varying the constraint, they could obtain any value of the dynamical collision rate; including the constraint makes WPMD an empirical model.…”
mentioning
confidence: 99%
“…In the following we simulate this quantum system using the Wave Packet Molecular Dynamics (WPMD) method. In contrast to earlier WPMD plasma models [8,12,17,29], the confined system formally does not introduce any wave packet broadening problem, since the width of the wave packets is naturally limited by the confinement walls. Moreover, the confined quantum system with infinite walls has no continuum spectrum of eigenstates, thus the partition function of this system can be unambiguously defined and calculated with controllable accuracy.…”
Section: Wave Packet Molecular Dynamicsmentioning
confidence: 93%
“…The peak at larger widths corresponds to propagating electrons. Their mean wave function width determines the strength of the effective interaction with ions and the electron-ion collision frequency [29]. This distribution may be accumulated by both Monte Carlo and dynamical versions of the method.…”
Section: Equilibration Of the Confined Quantum Systemmentioning
confidence: 99%
See 1 more Smart Citation